MEDIEVAL ISLAMIC AND CHRISTIAN RELATIONSHIP (International Conference on Social and Islamic Studies, 2022)
This paper describes the relationship between Muslims and Christians in the middle period of Islamic history (1250-1850). The two main points answered in this paper are, first; Relations between Muslims and Christians in the Era of Decline (1250-1500 AD) and, secondly, Relations between Muslims and Christians during the Three Great Kingdoms Period (1500-1800 AD). The method used is the method of writing history which includes heuristics, source criticism, interpretation and historiography. The historical method is useful for systematically and objectively reconstructing the past in order to reach a complete conclusion. The results of the study show that the relations between Islam and Christianity in the medieval period were more often confrontational than holding hands through a dialogical process. This period became a critical period for Muslims because it faced critical reciprocal tensions. Internally, Muslims are difficult to unite because of the diversity of cultures and the extent of their jurisdiction and the excessive fanaticism of religious groups. While external challenges, the Abbasid dynasty faced attacks from the Mongols led by Hulagu Khan and Timur Lenk as well as attacks from the Safavid Empire in Persia. Specifically, the confrontational relations between Islam and Christianity were marked by the collapse of the Ayubbiyah Dynasty. Since then, Muslims and Christians have increased the scale of conflict known as the Holy War or Crusade.